Pengaruh Penempatan Tenaga Kerja oleh Dinas Pendidikan terhadap Tenaga Pendidik dan Kependidikan - Heliwasnimar Heliwasnimar; Jamilus Jamilus (Departement of Mathematics Education, 2024)
Workplace placement is the process of assigning tasks and jobs to prospective workers who pass the selection to be carried out according to a predetermined scope, and are able to account for all risks and possibilities that occur regarding their duties and work, authority and responsibility, which is also a series of processes. after recruitment and selection to determine positions according to their abilities in order to complete work effectively and efficiently as determined by the organization. In the placement of workers, knowledge and experience and ability are needed in carrying out their duties and if experts are not doing it then there will be destruction or failure, so to achieve success you need the right placement according to their skills. This research is library research and is included in the qualitative research approach. Data collection was carried out directly from various relevant literature, including research articles. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and drawing conclusions. The results of data analysis show that workforce placement influences employee performance in education service agencies.